Investigating how climate change adaptation can be incorporated into mine closure and rehabilitation strategies to strengthen social-ecological resilience - Schulze, Megan (Stellenbosch : Stellenbosch University, 2023)
Thesis (MPhil)--Stellenbosch University, 2023.